Kicking velocity and physical, technical, tactical match performance for U18 female football players - Effect of a new ball - Andersen, T. B.; Bendiksen, M.; Pedersen, J. M.; Orntoft, C.; Brito, J.; Jackman, S. R.; Williams, C. A.; Krustrup, P. (Human Movement Science, 2012)
We investigated kicking velocity and physical, technical, and tactical match performance for under-18 (U18) female football players and evaluated the effect of using a newly developed lighter smaller ball. Ten regional league teams participated. Maximal ball velocity was 4 ± 1% higher when kicking the new ball (NB) compared with the standard ball (SB) in a laboratory testing situation (23.2 ± 0.4 vs. 22.4 ± 0.3 m s-1; p < .05). Mean HR was similar during games with NB and SB (169 ± 2 vs. 170 ± 2 b min-1; p > .05), but lower-limb muscular RPE was lower with NB (4.2 ± 0.4 vs. 5.2 ± 0.3; p < .05). The number of activity changes (1387 ± 76 vs. 1401 ± 55), total distance covered (9.09 ± 0.25 vs. 9.11 ± 0.25 km) and high-intensity running (1.04 ± 0.08 vs. 1.11 ± 0.07 km) were not different between NB and SB (p > .05). High-intensity running decreased (p < .05) from 0-20 to 60-80 min with NB (34%) and SB (37%). The number and success rate of long and short passes did not differ between NB and SB (p > .05). In conclusion, physiological demands were high in youth female football games, and decrements in running performance occurred towards the end of games. The players kicked faster and reported lower muscular exertion during games played with a lighter smaller ball, but locomotor activities, heart rate and overall technical-tactical game performance remained unaffected.